Nonword repetition and nonword reading abilities in adults who do and do not stutter - Sasisekaran, Jayanthi (2013)
PURPOSE: In the present study a nonword repetition and a nonword reading task were used to investigate the behavioral (speech accuracy) and speech kinematic (movement variability measured as lip aperture variability index; speech duration) profiles of groups of young adults who do (AWS) and do not stutter (control). METHOD: Participants were 9 AWS (8 males, Mean age = 32.2, SD = 14.7) and 9 age- and sex-matched control participants (Mean age = 31.8, SD = 14.6). For the nonword repetition task, participants were administered the Nonword Repetition Test (Dolloghan & Campbell, 1998). For the reading task, participants were required to read out target nonwords varying in length (6 vs. 11 syllables). Repeated measures ANOVA were conducted to compare the groups in percent speech accuracy for both tasks; only for the nonword reading task, the groups were compared in movement variability and speech duration. RESULTS: The groups were comparable in percent accuracy in nonword repetition. Findings from nonword reading revealed a trend for the AWS to show a lower percent of accurate productions compared to the control group. AWS also showed significantly higher movement variability and longer speech durations compared to the control group in nonword reading. Some preliminary evidence for group differences in practice effect (seen as differences between the early vs. later 5 trials) was evident in speech duration. CONCLUSIONS: Findings suggest differences between AWS and control groups in phonemic encoding and/or speech motor planning and production. Findings from nonword repetition vs. reading highlight the need for careful consideration of nonword properties.